DEEP LEARNING IMPLEMENTATION USING CONVOLUTIONAL NEURAL NETWORK IN DETECTING DISEASES IN POTATO LEAVES - Asep Juarna; Santi Dwi Agustin (Universitas Teknologi Mataram, 2023)
Potatoes are one of the tubers that planted on highland and lot of farmers who interesting because potatoes have stable value of selling. Based of Kementan notes (2018) that often failed harvest happened on farmers of potatoes. This research will explaining about diseases classification on leaves of potatoes using Convolutional Neural Networks (CNN) which is deep learning neural network. The purpose of this research is ti develop model of artificial neural network using Backpropagation and high accuracy CNN method. The model’s parameters has 75 epochs and 30 batch_size while the activation modes uses Relu and Softmax ones. Evaluation of the model’s scores are 100% of training image and 96% of testing or validation image.